2015
DOI: 10.1039/c4nr05712k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in carbon nanodots: synthesis, properties and biomedical applications

Abstract: Herein, a mini review is presented concerning the most recent research progress of carbon nanodots, which have emerged as one of the most attractive photoluminescent materials. Different synthetic methodologies to achieve advanced functions and better photoluminescence performances are summarized, which are mainly divided into two classes: top-down and bottom-up. The inspiring properties, including photoluminescence emission, chemiluminescence, electrochemical luminescence, peroxidase-like activity and toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
264
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(269 citation statements)
references
References 100 publications
3
264
0
2
Order By: Relevance
“…[4] To this end, the past two decades have served as atest-bed for measuring the physico-chemical properties of carbon in reduced dimensions starting with the advent of fullerenes (0D), followed, in chronological order, by carbon nanotubes (1D), graphene (2D), and recently carbon nanodots (0D/2D). [5,6] These species are now poised for use in aw ide range of applications. [1] Thed esign of new,s imple,a nd inexpensive photosensitizers is important, especially in the conversion of solar energy for emerging areas,s uch as light harvesting,e nergy storage, and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[4] To this end, the past two decades have served as atest-bed for measuring the physico-chemical properties of carbon in reduced dimensions starting with the advent of fullerenes (0D), followed, in chronological order, by carbon nanotubes (1D), graphene (2D), and recently carbon nanodots (0D/2D). [5,6] These species are now poised for use in aw ide range of applications. [1] Thed esign of new,s imple,a nd inexpensive photosensitizers is important, especially in the conversion of solar energy for emerging areas,s uch as light harvesting,e nergy storage, and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique surface chemistry of C-dots (that is, the carboxylate groups and sp 2 framework), 217 aromatic molecules (chemical drugs and dyes) tend to adsorb onto C-dots through a set of noncovalent chemical interactions, including electrostatic interactions between carboxylate groups at the C-dot surface and positively charged residues, as well as van der Waals interactions between the hydrophobic moieties of the molecule proteins and C-dots. In fact, Choi et al 218 demonstrated that the ZnPc PSs-capped C-dot composite could be used for dual color bioimaging (λem = 461 nm and λex = 358 nm for C-dots and λem = 665 nm and λex = 647 nm for ZnPc) and ZnPc-assisted PDT (10 min with a 660 nm laser at 30 mW cm − 2 ).…”
Section: Nir-absorbing Organic Materials: Dyes and Polymersmentioning
confidence: 99%
“…In contrast, graphene and carbon nanotube exhibited higher sensitivity, but their poor dispersibility in aqueous solution decreased the spot-to-spot reproducibility, and the ionization efficiency was often affected by their different structural properties [19,21]. Carbon nanodots (CDs), which is a new form of zero-dimensional carbonaceous nanomaterial, possesses a variety of advantages, including convenient sample synthesis, excellent water dispersibility, and photostability [22,23]. Recently, Nie's group firstly used CDs as a novel matrix for the analysis of a series of LMW compounds by MALDI-TOF MS with higher sensitivity over other reported carbon based matrices [24].…”
mentioning
confidence: 99%